An Instructional Design Approach to Updating an Online Course Curriculum - Hai-Jew, Shalin (My University, 2011)
A well-designed curriculum for online learning nurtures both student learning and student retention. While ideally value will be designed into an online curriculum from the start, the reality is that, across the spectrum of e-learning, there is a wide range of quality. Consequently, virtually every online course can benefit from periodic curricular updates. Once online courses are developed and implemented, however, their curriculum might not be changed or updated for some time, if ever. When it does take place, curricular redesign tends to focus on particulars rather than the big picture. Rarely do we step back to fundamentally assess the raison d'etre for a given curriculum — to examine the essential cultural factors that undergird that curriculum and the purposes for which it was created.1 Analyses at that level have great potential to enrich a curriculum. In addition, curricular updates can introduce important new content, and may also introduce pedagogical enhancements that can improve the quality of e-learning. In this context, this article presents ideas for an approach based in the principles of instructional design to updating the curriculum for online courses. Tools from that realm — including establishing processes for effective online learning, templating digital learning objects and modules for quality, defining clear work flows and decision junctures, adhering to standards of legality and ethics, and applying wise leadership and project management—offer a powerful approach to the development and refinement of quality curricula.
Keywords: Electronic learning; Instructional design; Online courses; Curriculum development; Course organization; Change strategies; Educational strategies; Curriculum design